2017
DOI: 10.1002/hon.2438_90
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Follicular Lymphoma (Fl) in Maintained Complete Response (Cr) at 30 Months Show a Survival Similar to a Sex‐ and Age‐matched Spanish General Population

Abstract: No significant difference in OS was observed between the 2 groups for patients not having received rituximab in first line. These data suggest that among patients treated with rituximab, despite an identical PFS, survival outcomes were statistically higher in the <40 group compared to 40-60.Conclusions: This study reports the clinical characteristics and outcomes in the most important cohort of young patients aged <40 with first-line FL. Age <40 y did not appear to influence the treatment outcome, but was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similar results described in other series confirmed that the outcome of patients who progress early is very unfavourable (Jurinovic et al, 2016) (Maurer et al, 2016). Conversely, more recently, we observed that patients in CR after the maintenance period, at 30 months from the start of therapy, had a remarkably favourable OS, similar to that of the general population (Magnano et al, 2017). The data herein presented are a confirmation of the same tendency along the course of the disease: the shorter the RD, the shorter the survival at any phase of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results described in other series confirmed that the outcome of patients who progress early is very unfavourable (Jurinovic et al, 2016) (Maurer et al, 2016). Conversely, more recently, we observed that patients in CR after the maintenance period, at 30 months from the start of therapy, had a remarkably favourable OS, similar to that of the general population (Magnano et al, 2017). The data herein presented are a confirmation of the same tendency along the course of the disease: the shorter the RD, the shorter the survival at any phase of the disease.…”
Section: Discussionsupporting
confidence: 91%